The Integration of Living Environmental Education in the Behavior of High School Students in Brebes Regency - Leksono, Karyono Budi; Setyowati, Dewi Liesnoor; Hardati, Puji (JESS (Journal of Educational Social Studies), 2020)
Life environment education gains the main priority for formal education. For school stakeholders, this condition should be responded to immediately. Schools have to struggle to improve their learners’ environmental awareness. This research describes and analyzes the Living Environmental education policy, its integration to a geographic lesson, and learners’ environmental awareness behaviors of Senior High Schools in Brebes. This research is qualitative. The data were collected by interviewing, observing, and studying the document. The applied data analysis stages were data reduction, display, and conclusion. The findings showed that 1) the Living Environmental education policy was determined by the school since there were no obligated rules from the government. 2) Living Environmental education integration had been promoted well in a geography lesson. It was realized into learning instrument administration and the learning process. This life environment education could be integrated into almost all basic competencies of all geographic materials. 3) learners were aware of a better living environment. They were aware and could understand the problems and negative impacts. In addition to these, learners also acted and were committed to keeping their life environment.